VKORC1 gene polymorphism (-1639G>A) in warfarin therapy patients of Pakistani population - Muhammad Bilal Ghafoor; Faiza Yasmeen; Abdul Wadood Khalid; Ghulam Mustafa; Shagufta Khaliq; Shahida Mohsin (Journal of the Pakistan Medical Association, 2022)
Objective: To observe vitamin K epoxide reductase complex subunit 1-1639 G>A polymorphism in patients resistant to warfarin therapy, and to calculate the allele frequency of the polymorphism in local patients. Method: The cross-sectional case-control study was conducted at the Punjab Institute of Cardiology, Lahore, from 2013 to 2014, and comprised patients with heart valve replacement. Thy were divided into warfarin-resistant group 1 taking 10mg/day, 70mg/week, and control group 2 taking a standard dose of 5mg/day, 35mg/week. The vitamin K epoxide reductase complex subunit 1-1639 G>A polymorphism analysis was done by polymerase chain reaction, followed by restriction fragment length polymorphism technique. Data was analysed using SPSS 20. Results: Of the 146 patients, there were 73(50%) in each of the two groups. In group 1, there were 37(50.68%) males and 36(49.32%) were females with an overall mean age of 33±12 years, while group 2 had 36(49.32%) males and 37(50.68%) females with an overall mean age of 37±13 years. There were no significant differences in mean values of age, serum cholesterol, triglycerides and albumin levels between the groups (p>0.05). The G allele was the most frequently found in both groups, with 140(96%) in group-1 and 137(94%) in group-2. Overall, the homozygous GG genotype was significantly higher in the sample 132(90.4%) (p<0.05). Conclusions: There was evidence found that vitamin K epoxide reductase complex subunit 1-1639 G>A polymorphism alone may not be the dominant genetic factor associated with warfarin response variability. Key Words: Warfarin, VKORC1 gene, Single nucleotide polymorphism, PCR-RFLP.